Type‐2 Diabetes and Identification of Major Genetic Determinants of Glycemic Index in Rice – A Review. (1st May 2022) - John, Deepa; Sureshkumar, S.; Raman, Maya
Abstract: Rice consumers of different parts of the world always face the risk of diabetes and related health complications. Dietary intervention is the best adapted measure to maintain blood glucose levels and manage the diseases in rice consuming populations. The glycemic index of rice varieties is negatively correlated to the amylose content. Research studies have proven that the consumption of rice varieties with low glycemic index has beneficial effects in controlling diabetes. The genetic basis for the diversity observed for amylose content in different rice varieties is well elucidated. Waxy gene (Wx) is known to encode Granule–Bound Starch Synthase I (GBSS I) enzyme, which determines the amylose content in rice. Different allelic variations of Wx gene exist, which can be correlated to varying amylose content in rice. The PCR‐based markers for detecting single nucleotide polymorphism mutation at Wx locus provides a cost‐effective alternative to genotype rice varieties. This review outlines the anti‐diabetic properties of rice and strategies to identify rice varieties with a low glycemic index at the molecular level. The molecular basis of the glycemic index allows breeders to successfully identify rice germplasms with low glycemic index and engineer rice varieties with high grain yield and low glycemic index. Abstract : DNA from rice varieties are subjected to PCR amplification with molecular markers linked to the waxy locus. Varieties are classified into low, intermediate, and high amylose content based on the polymorphism. A spectrophotometric method is also adopted to classify the rice varieties based on amylose content. Consumption of high amylose rice varieties lowers glycemic index and is therefore, recommended to diabetic subjects.